Efficacy and Safety of Albendazole in Hookworm-infected Preschool-aged Children, School-aged Children, and Adults in Côte d'Ivoire: A Phase 2 Randomized, Controlled Dose-finding Trial. (15th July 2020) - Patel, Chandni; Coulibaly, Jean T; Hofmann, Daniela; N'Gbesso, Yves; Hattendorf, Jan; Keiser, Jennifer
Abstract: Background: Infections with hookworms affect about half a billion people worldwide. Recommended therapy includes 400 mg of albendazole, which is moderately efficacious. Higher doses have been rarely assessed. Methods: A randomized, controlled dose-finding trial was conducted in Côte d'Ivoire with the aim of recruiting 120 preschool-aged children (PSAC), 200 school-aged children (SAC), and 200 adults. Eligible PSAC were randomized 1:1:1 to 200 mg, 400 mg, or 600 mg of albendazole; the other age groups were randomized 1:1:1:1:1 to placebo or 200 mg, 400 mg, 600 mg, or 800 mg. The primary outcome was cure rates (CRs) assessed 14–21 days post-treatment by quadruplicate Kato-Katz thick smears. Hyperbolic E max models were used to determine dose-response. Results: 38 PSAC, 133 SAC, and 196 adults were enrolled. In adults, predicted CRs increased with ascending doses of albendazole, with a CR of 74.9% (95% confidence interval [CI], 55.6%–87.7%) in the 800-mg arm. Observed CRs increased with ascending doses of albendazole reaching a maximum of 94.1% (95% CI, 80.3%–99.3%). In SAC, the predicted dose-response curve increased marginally, with CRs ranging from 64.0% in the 200-mg arm to 76.0% in the 800-mg arm. Sample size in PSAC was considered too small to derive meaningful conclusions. 10.7% and 5.1% of participants reported any adverse event at 3 hours and 24 hours post-treatment, respectively. Conclusions: A single 800-mg albendazole dose provides higher efficacy against hookworm and is well tolerated in adults and should be considered for community-based strategies targeting adults. For PSAC and SAC, current recommendations suffice. Clinical Trials Registration: NCT03527745. Abstract : A higher dose of albendazole in adults for the treatment of hookworm infection provides increased cure rates with high tolerability, whereas an increase in dose does not provide additional benefit in children.